2014
DOI: 10.3310/hta18450
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation in pregnancy: a systematic review

Abstract: 1. ABSTRACT Background It is unclear whether the current evidence base allows definite conclusions to be made regarding the optimal maternal circulating concentration of 25(OH)-vitamin D during pregnancy, and how this might best be achieved. CRD42011001426. Aim/ Research Questions What are the clinical criteria for vitamin D deficiency in pregnant women?What adverse maternal and neonatal health outcomes are associated with low maternal circulating 25(OH)-vitamin D?Does maternal supplementation with vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
237
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(252 citation statements)
references
References 138 publications
(268 reference statements)
6
237
2
7
Order By: Relevance
“…Thorne-Lyman and Fawzi (7) evaluated observational studies and RCTs and found an association of vitamin D supplementation and diet, with a lower incidence of low birth weight; other outcomes were not significantly affected by the interventions. Finally, Harvey et al (10) assessed observational studies and RCTs for the effect of serum vitamin D levels, or supplementation of women with vitamin D or food containing vitamin D on maternal and neonatal outcomes. In comparison with these 3 earlier systematic reviews (Supplemental Table 2, available online), the current metaanalysis predefined several other relevant maternal and neonatal outcomes, excluded observational studies that were prone to several biases, and included a larger number of RCTs and time spans ranging to as recently as 2014.…”
Section: Limitations Of Previous Meta-analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thorne-Lyman and Fawzi (7) evaluated observational studies and RCTs and found an association of vitamin D supplementation and diet, with a lower incidence of low birth weight; other outcomes were not significantly affected by the interventions. Finally, Harvey et al (10) assessed observational studies and RCTs for the effect of serum vitamin D levels, or supplementation of women with vitamin D or food containing vitamin D on maternal and neonatal outcomes. In comparison with these 3 earlier systematic reviews (Supplemental Table 2, available online), the current metaanalysis predefined several other relevant maternal and neonatal outcomes, excluded observational studies that were prone to several biases, and included a larger number of RCTs and time spans ranging to as recently as 2014.…”
Section: Limitations Of Previous Meta-analysesmentioning
confidence: 99%
“…The effects of vitamin D supplementation on maternal and neonatal outcomes in randomized controlled trials (RCTs) have been previously examined in 3 systematic reviews and/or meta-analyses (7,9,10). These studies had several limitations, including deficiencies in study design (inclusion of quasi-randomized trials and observational studies), and are restricted by the outcomes evaluated.…”
mentioning
confidence: 99%
“…There is also a body of research linking suboptimal vitamin D during pregnancy with increased risk of pregnancy related disorders such as gestational diabetes, pre-eclampsia and offspring being small for gestational age (Aghajafari et al, 2013, Wei et al, 2013, Harvey et al, 2014 and other research linking suboptimal vitamin D levels early in life with adverse health outcomes later in life (Boucher, 1998, McGrath, 2001, Brannon and Picciano, 2011, Christesen et al, 2012, Thorne-Lyman and Fawzi, 2012, Zipitis and Akobeng, 2008, Ponsonby et al, 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Larger-scale clinical trials of vitamin D supplementation during pregnancy that systematically measure skeletal mineral content and morphology in newborns, and larger and carefully executed associational studies, are needed to be certain whether vitamin D deficiency in utero has any effects on skeletal mineralization at term or later in childhood. Several systematic reviews agree with the conclusion that current data are insufficient to know if vitamin D supplementation during pregnancy confers any skeletal or nonskeletal benefits on fetuses (244,560,561).…”
Section: F Summary Of Key Pointsmentioning
confidence: 94%